2005
DOI: 10.1248/bpb.28.1813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antifungal Drugs on Cytochrome P450 (CYP) 1A2, CYP2D6, and CYP2E1 Activities in Human Liver Microsomes

Abstract: Antifungal drugs, including fluconazole, itraconazole, micafungin, miconazole, and voriconazole, are widely used in the treatment of systemic candidal infections and mycoses. The mechanism of action of these antifungal drugs except for micafungin is the inhibition of fungal cytochrome P450 (CYP, 14a-sterol demethylase), an enzyme responsible for the conversion of lanosterol to 14a-demethyllanosterol in the ergosterol biosynthetic pathway, 1,2) whereas micafungin inhibits 1,3-b-D-glucan synthase, leading to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…44 Interactions may also unexpectedly occur among commonly prescribed, as well as OTC, medications during pregnancy. Yeast infections are treated with fluconazole and miconazole, which inhibit key CYP enzymes involved with 45 Such interactions may increase maternal plasma levels, potentially also affecting fetal plasma concentrations, and the risk of drug-elicited adverse effects, with consequences for fetal cardiovascular, neurologic, endocrine, or metabolic function.…”
Section: Sri-drug Interactionsmentioning
confidence: 99%
“…44 Interactions may also unexpectedly occur among commonly prescribed, as well as OTC, medications during pregnancy. Yeast infections are treated with fluconazole and miconazole, which inhibit key CYP enzymes involved with 45 Such interactions may increase maternal plasma levels, potentially also affecting fetal plasma concentrations, and the risk of drug-elicited adverse effects, with consequences for fetal cardiovascular, neurologic, endocrine, or metabolic function.…”
Section: Sri-drug Interactionsmentioning
confidence: 99%
“…This reaction is mainly catalyzed by CYP3A (60%), but the rest is catalyzed equally between CYP2C9, CYP2C19, CYP2D6, and CYP1A2 [2,3]. Correspondingly, previous in vitro studies have indicated that miconazole is a nonselective inhibitor of several CYPs, namely CYP3A, 2C9, 2C19, 1A2, 2A6, and 2B6 [4][5][6]. In our study, after 3-day pretreatment with miconazole oral gel (3.5 ml ≈ 85 mg three times daily), miconazole plasma concentrations were quantifiable (4 ng/ml or more, data not shown) up to 24 h after the last dose and were sufficient to cause similar increase in the concentrations of etoricoxib than systemic oral voriconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Timed blood samples were drawn immediately before and at 0.5, 1, 1.5, 2, 2.5, 3,4,5,6,8,12,24,48, and 72 h after etoricoxib administration. After 12 h, blood samples were drawn by venipuncture.…”
Section: Sampling and Drug Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Miconazole has been reported to inhibit several CYP-enzymes in human liver or lymphoblast microsomes in vitro, including CYP1A2 and CYP3A4, with an inhibition constant (K i ) of 3.2 and 0.028 µM [14] and a half maximal inhibitory concentration (IC 50 ) of 2.9 and 0.074 µM [41,42], respectively. This indicates, that miconazole in the mean absorbed concentration of 12.9 µg/L serum corresponding to 0.03 µM could have an effect on the enzymes in vivo also.…”
Section: Discussionmentioning
confidence: 99%